Biological Functionalization of Dental Implants with Fibronectin: A Scanning Electron Microscopic Study - Elkarargy, Amr Anas (International Journal of Health Sciences, 2014)
<!–[if gte mso 9]> <![endif]–> Objectives:Â Early stages of peri-implant bone formation play an essential role in the osseointegration and long-term success of dental implants. Biological implant surface coatings are an emerging technology to enhanceÂ the attachment of the implant to the surrounding bone and stimulate bone regeneration. The purpose of this study was to determine the effect of coating the implant surface with fibronectin on osseointeÂgration. Material and methods: The experiment was conducted on a total of twelve New Zealand white mature male rabbits, weight between 2.5-4 kg. Twenty four pure titanium implants were used in this study. Each rabbits received two implants, one implant in each tibia; the implant in the right limb was coated with fibronectin (experimental group), whilst on the contralateral side the implants were placed without coating (control group). Six rabbits were sacrificed for Scanning Electron Microscopic evaluation after 4 and 8 week healing periods. Results: The results of the present study demonstrating the mean gap distance between the bone and implant was greater in the control group compared to fibronection group at both observation periods however, the difference between these two groups was not statistically significant. Conclusion: Thus, it could be suggested that the biological functionalization of dental implants with fibronectin, may influence the integration or biocompatibility and bonding of the implant to the surrounding bone. Keywords: Dental implant, Osseointegration, Biofunctionalization, Extracellular matrix, Fibronectin. <!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>